Developing Local Wisdom-Based Augmented Reality Modules for Science and Social Studies Learning in Elementary Schools - Nurul Mahruzah Yulia; Suttrisno Suttrisno (STAI Hubbulwathan Duri, 2024)
This study aims to develop and evaluate a local wisdom-based science learning module integrated with augmented reality (AR) for Grade V elementary school students. The module incorporates elements of Bojonegoro's natural and social environment to enhance contextual learning. The research employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with a sample of 100 students from three elementary schools in Bojonegoro. The development process included analyzing student needs, designing, validating, and revising the module before implementation and evaluation. Validation involved assessments from IT learning method experts, science education experts, and practitioners. Validation results indicated the module was highly suitable for use: 95% were from IT experts, 90% were from science education experts, and 94% were from practitioners. Implementation demonstrated significant improvements in students’ science learning outcomes, with an average score increase from 56 to 88. Additionally, the module enhanced student motivation (92%) and participation (96%) during the learning process. The integration of augmented reality in the module effectively addressed limitations in real-world observation, engaging students and diversifying science learning media. The module’s emphasis on local wisdom further enriched students' understanding of their cultural and environmental context. The developed AR-based local wisdom science module is an effective and engaging tool for improving learning outcomes and fostering motivation among elementary school students.